UMKM Financial Management Strategies In Digital Economy And Uncertainty - Zacky, Muhamad (Utami Publisher, 2025)
The digital transformation and global economic instability have created both challenges and opportunities for Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. This article aims to explore financial management strategies that MSMEs can use to survive and grow in an uncertain digital economy. This research applies a qualitative descriptive approach through a literature review of relevant journals in the past five years. The findings show that financial digitalization, adaptive cash flow management, and the use of financial technology are effective main strategies. Additionally, the importance of digital financial literacy and financial planning responsive to external risks are key success factors for MSMEs. The study recommends collaboration between the government, financial institutions, and digital platforms to enhance MSMEs’ competitiveness through integrated and innovative financial strategies.